Experimental study on the efficiency of tapered strip dampers for the seismic retrofitting of damaged non-ductile RC frames. (15th November 2019) - Vafaei, Mohammadreza; Omar Sheikh, Abdirahman Mursal; C. Alih, Sophia
Highlights: A full-scale RC frame was constructed and subjected to the reversed cyclic loading. The damaged RC frame was retrofitted by a tapered strip damper (TSD). The lateral stiffness and strength of the retrofitted frame were estimated accurately. An enhanced strength and displacement capacity were obtained for the retrofitted frame. Superior energy dissipation was observed for the retrofitted frame. Abstract: Many non-ductile reinforced concrete (RC) frames were significantly damaged in past earthquakes. Although demolishing of such damaged structures has become common practice, it results in a significant amount of economic loss. The efficiency of using tapered strip damper (TSD) for seismic retrofitting of damaged RC frames is investigated in this study. A full-scale one-bay single-story non-ductile RC frame was constructed and subjected to quasi-static cyclic loading until it reached its ultimate load. A specially designed TSD was used in retrofitting the damaged frame. The retrofitted frame was subjected to a similar cyclic loading, and its response was recorded. The experimental results are very similar to the analytically calculated values for the lateral stiffness and ultimate strength of the retrofitted frame. Besides, the retrofitted frame exhibited higher lateral strength and displacement capacity compared with the reference RC frame. Compared with the reference frame, the stiffness degradation of the retrofitted frame was slower, and its energy dissipation was superior. It was concluded that the employed TSD was effective in retrofitting the damaged non-ductile RC frame.